HUBUNGAN C-REAKTIF PROTEIN TERHADAP PROSES PENYEMBUHAN LUKA KAKI DIABETIK: PILOT STUDY - Arisandi, Defa; Amaludin, Mimi; Alfikrie, Fauzan; Akbar, Ali; Hatmalyakin, Debby; Hidayat, Uti Rusdian; Nurpratiwi, Nurpratiwi (Jurnal Keperawatan dan Kesehatan, 2023)
Background: Diabetic foot ulcer (DFU) is a major complication in patients with diabetes mellitus which has a significant impact on quality of life with the main complication being the risk of amputation. C-Reactive Protein (CRP) is one of the most widely used markers of inflammation. With DFU of any severity. Objective: The aim of this study was to determine the relationship between the value of C-reactive protein (CRP) and the healing of diabetic foot ulcer. Methods: The type of research used is an analytic observational study with a cross-sectional approach, where data relating to independent and dependent variables will be collected at the same time. This research was conducted at a clinic in Pontianak City. The number of samples is 23 respondents. Data collection was carried out by conducting interviews for data on the characteristics of the respondents. For data on the characteristics of the ulcer, it was carried out using observation techniques. CRP data was taken from secondary data from laboratory examination of patients when they first came to the clinic. Data from respondents will be analyzed using the SPSS program with the test used to test the hypothesis is the bivariate test with the Pearson product moment test. Result: CRP value with diabetic foot ulcer healing experienced by a person with the results of bivariate analysis using the Pearson product moment test shows a p value of 0.74. Conclusion: There is a relationship between C-Reactive Protein (CRP) on diabetic foot ulcer healing.